Produksi Etanol Dari Jus Pelepah Sawit Menggunakan Bakteri Kultur Tercampur Rumen Sapi - Anysha Lankari Halim; David Andrio; Said Zul Amraini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Oil Palm Fronds are the largest source of biomass waste in the palm oil industry. Oil Palm Frond Juice has high simple sugar content with a total COD content of 63,000 mg / L potentially as a medium for bioethanol fermentation. Ethanol fermentation with the use of pure bacterial culture requires aseptic conditions so it is difficult to maintain causing ineffective ethanol production. One solution is to use mixed bacterial cultures. This research aimed to study of the use of mixed cultures on bioethanol production, COD removal, TAV formation and VSS growth using cattle rumen. In this study the process of seeding was carried out for 5 days in a Circulating Bed Reactor (CBR) with working volume of 25 liters by adding glucose (C6H12O6) at the beginning of the process with comparison of the ratio of biomass and substrate 80: 20 (% v/v). The fermentation process of oil palm frond juice is carried out in batch using an erlenmeyer with a working volume of 150 ml containing substrate and biomass at a ratio of 70: 30 (% v/v) under conditions of room temperature. pH controlled at 5 which is natural pH of the oil palm frond juice. Bioethanol concentration was analyzed using High Performance Liquid Chromatography (HPLC). The results of the main study showed the efficiency of total COD removal, dissolved COD removal and VFA production respectively at 32.35%; 32.32% and 39.13%, with the VSS growth rate of 1444.44 mg/L. The final bioethanol concentration was 498.07 mg/L which is very low compared to using pure culture. These resulst indicate there is a need for ways to increase ethanol production using mixed cultures.Keywords: Palm frond juice, ethanol production, anaerobic fermentation, mixed culture bacteria.